Genome-wide characterization and analysis of Golden 2-Like transcription factors related to leaf chlorophyll synthesis in diploid and triploid Eucalyptus urophylla - Liu, Zhao; Xiong, Tao; Zhao, Yingwei; Qiu, Bingfa; Chen, Hao; Kang, Xiangyang; Yang, Jun (Frontiers in Plant Science, 2022)
Golden 2-Like (GLK) transcription factors play a crucial role in chloroplast development and chlorophyll synthesis in many plant taxa. To date, no systematic analysis of GLK transcription factors in tree species has been conducted. In this study, 40 EgrGLK genes in the Eucalyptus grandis genome were identified and divided into seven groups based on the gene structure and motif composition. The EgrGLK genes were mapped to 11 chromosomes and the distribution of genes on chromosome was uneven. Phylogenetic analysis of GLK proteins between E. grandis and other species provided information for the high evolutionary conservation of GLK genes among different species. Prediction of cis-regulatory elements indicated that the EgrGLK genes were involved in development, light response, and hormone response. Based on the finding that the content of chlorophyll in mature leaves was the highest, and leaf chlorophyll content of triploid Eucalyptus urophylla was higher than that of the diploid control, EgrGLK expression pattern in leaves of triploid and diploid E. urophylla was examined by means of transcriptome analysis. Differential expression of EgrGLK genes in leaves of E. urophylla of different ploidies was consistent with the trend in chlorophyll content. To further explore the relationship between EgrGLK expression and chlorophyll synthesis, co-expression networks were generated, which indicated that EgrGLK genes may have a positive regulatory relationship with chlorophyll synthesis. In addition, three EgrGLK genes that may play an important role in chlorophyll synthesis were identified in the co-expression networks. And the prediction of miRNAs targeting EgrGLK genes showed that miRNAs might play an important role in the regulation of EgrGLK gene expression. This research provides valuable information for further functional characterization of GLK genes in Eucalyptus.